Metabolismo do acetato entre membros do gênero paracoccidioides spp - Mata, Fabiana Ribeiro da (2017)
Members of the genus Paracoccidioides are known pathogens of humans that can be isolated from different infection sites. To investigate the expression rates of proteins expressed by different isolates, of the genus Paracoccidioides, including one isolate of P. lutzii (Pb01), and three isolates of P. brasiliensis (Pb03, Pb339 and PbEPM83) using sodium acetate, as carbon source, proteins quantities were determined using label-free and data independent LC-MSE. Statistical analysis provided the comparison of proteins profiles in the isolates. A total of 1160, 1211, 1280 and 1462 proteins were reproducibly identified, and relatively quantified in P. lutzii e P. brasiliensis isolates Pb03, Pb339 e PbEPM83, respectively. Notably, a total of 526, 435, 744 and 747 proteins were differentially expressed among P. lutzii and the P. brasiliensis isolates Pb03, Pb339 and PbEPM83, respectively with a fold change equal or higher than 1.5. The analysis revealed the reorganization of metabolism through the induction of proteins related to gluconeogenesis, stress response and amino acid degradation in the four isolates evaluated. The differences between the isolates were observed as follows: greater increases in the expression levels of proteins belonging to the cycle of glyoxalate, TCA and respiratory chain, ethanol production and β-oxidation were observed in the isolatesPPEPM83 and Pb01; Cyclic and cyclocyclic proteins of the methylcitrate were induced in Pb339. Proteomic profiles indicate that the four isolates reorganize the metabolism for the use of acetate as a carbon source.